Digestibility of different fats and fatty acids in the blue fox (Alopex lagopus) - Rouvinen, Kirsti; Kiiskinen, Tuomo; Mäkelä, Jaakko (The Scandinavian Association of Agricultural Scientists (NJF), 1988)
V ok